2017
DOI: 10.1016/j.biopsych.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and Imipramine Reverse Transcriptional Signatures of Susceptibility and Induce Resilience-Specific Gene Expression Profiles

Abstract: Background Examining transcriptional regulation by antidepressants in key neural circuits implicated in depression, and understanding the relationship to transcriptional mechanisms of susceptibility and natural resilience, may help in the search for new therapeutics. Given the heterogeneity of treatment response in human populations, examining both treatment response and non-response is critical. Methods We compared the effects of a conventional monoamine-based tricyclic antidepressant, imipramine, and a rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
114
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 51 publications
8
114
0
Order By: Relevance
“…Bagot et al (71) have used a model based on a social-interaction paradigm, subjecting the mice to a chronic social defeat stress to induce a depression-like state. This is likely to induce transcriptional responses that differ from our mice, because we used an experimental paradigm that does not include chronic stress (72).…”
Section: Discussionmentioning
confidence: 99%
“…Bagot et al (71) have used a model based on a social-interaction paradigm, subjecting the mice to a chronic social defeat stress to induce a depression-like state. This is likely to induce transcriptional responses that differ from our mice, because we used an experimental paradigm that does not include chronic stress (72).…”
Section: Discussionmentioning
confidence: 99%
“…For gene expression studies involving chronic imipramine treatments in behaviorally susceptible animals, NAc RNA was obtained from behavioral "responders," as determined in a recently published study (13). For ChIP-seq experiments, control and susceptible mice (determined in SI test 48 h postdefeat) were killed 28 d following the final defeat episode.…”
Section: Methodsmentioning
confidence: 99%
“…Future investigations will require the inclusion of both sexes in animal testing (Hodes et al, 2017), but it is interesting to note that in a mouse model of depression during menopause, Miyata et al (2016b) also found that the gene expression alterations induced by ovariectomy were mainly associated with ribosomal and mitochondrial functions in both the medial prefrontal cortex and the blood, strengthening the results we discussed above. We also only addressed the response to antidepressant treatment with a single drug, fluoxetine, while other drugs with different selectivity for neurotransmitters other than serotonin are frequently used in the clinic (Bagot et al, 2017). Other modalities such as repeated transcranial magnetic stimulation have been increasingly proposed, especially to patients resistant to first and second-line antidepressant drug treatments.…”
Section: Discussionmentioning
confidence: 99%